To Cement or Not? Five-Year Results of a Prospective, Randomized Study Comparing Cemented vs Cementless Total Knee Arthroplasty - Fricka, Kevin B.; McAsey, Craig J.; Sritulanondha, Supatra (The Journal of arthroplasty, 2019)
The optimal mode of fixation in total knee arthroplasty is a continuing subject of debate. Previously, we reported 2-year results for this prospective, randomized trial. Knee Society Scores, Oxford scores, and pain visual analog scales were collected pre-operatively and post-operatively. Minimum 5-year follow-up has been obtained with radiographic analysis for 85 patients. Mean Knee Society Scores and Oxford scores and patient-reported outcomes were similar in both groups. Each group had 1 additional revision, but neither was related to implant fixation. Survivorship with revision as an endpoint was equivalent (95.9% and 95.3%, P = .98). There was no significant difference in radiolucencies observed between groups (P = .10), all were non-progressive. Cementless and cemented total knee arthroplasty had equivalent patient-reported outcomes and survivorship at midterm follow-up. Updates are planned at 10 and 15-year intervals to observe long-term modes of failure between these 2 methods of fixation.